An activatable polymeric nanoprobe for fluorescence and photoacoustic imaging of tumor-associated neutrophils in cancer immunotherapy - Zhang, Yan (2022)
Imaging to evaluate tumor-associated neutrophils (TANs) is imperative for cancer immunotherapy but remains challenging. We herein report an activatable semiconducting polymer nanoprobe (SPCy) for near-infrared fluorescence (NIRF) and photoacoustic (PA) imaging of neutrophil elastase (NE), a biomarker of TANs. SPCy comprises a semiconducting polymer conjugated with a hemicyanine (hemi-Cy) dye caged by a NE-cleavable peptide as the side chain. After systemic administration, SPCy passively targets the tumor and reacts with NE to "uncage" the hemi-Cy, leading to enhanced NIRF and PA signals of the hemi-Cy but unchanged signals of the SP. Such NE-activated ratiometric NIRF and enhanced PA signals of SPCy correlate with the intratumoral population of TANs. Thus, this study not only presents the first TAN-specific PA probe, but also provides a general molecular design strategy for PA imaging of other immune-related biomarkers to facilitate screening of cancer immunotherapeutics.